ANALISIS RESEPSI KHALAYAK TERHADAP VIDEO "CARA BERJALAN YANG NYAMAN" DI YOUTUBE FIERSA BESARI (Studi Analisis Resepsi Terhadap Pendaki) - Melvin Ericson (2022)
This study aims to determine the audience's position in receptive to the show "Cara Berjalan Yang Nyaman" and determine the audience's reception of the show. The purpose of analyzing the reception of climbers is to find out what is informed in the show whether or not it is suitable for beginner climbers and a reminder for senior climbers. The method used in this research is a qualitative method with a Reception Analysis study approach. The concept in this study uses the concepts of Mass Communication, New Media, Reception Analysis and Youtube. This research uses the Reception Analysis theory proposed by Stuart Hall and groups the audience into 3 existing categories. Namely, dominant position, negation, and opposition. The result of this research is that there are informants who fall into these three categories and perceive the impressions differently because the experience of the informants and the knowledge of the informants are also different.